"Akadémiai etika és integritás" – gondolatok egy új egyetemi tantárgy margójára - Sarolta PÜSÖK (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2021)
Academic Ethics and Integrity – Thoughts on a New University Course. The study discusses the origin and the necessity for the subject Academic Ethics and Integrity by presenting the highlights of professional discourses of the Hungarian and Romanian language area. The cited literature shows that in the last decades’ research ethics and integrity have been breached in many ways. The crisis management strategy involves the enactment of a law that introduces Academic Ethics and Integrity as a compulsory university subject. The present study delineates the topics related to the subject (e.g. questions regarding the integrity of researcher/teacher and publishing activity; legal documents, presentation of the organizations), but the most important scope was to adjust the topics of the subject to the particular situation of the faculties of theology. Thus, the new compulsory subject offers freedom to raise awareness about the meaning of theology and its role in society and academic setting. Lastly, it is argued that the subject gives excellent space for debating and construing questions of intellectuality in the 21st century.